Research progress on the relationship between chronic prostatitis/chronic pelvic pain syndrome and the microbiota of the reproductive system - Song, Wei-Jie; Liu, Xin-Yi; He, Le-Ye (Frontiers in Cellular and Infection Microbiology, 2024)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common pelvic pain syndrome in males, seriously affecting patients’ quality of life. For a long time, CP/CPPS has been considered a complex and variable disease, and its pathogenesis remains incompletely understood. Currently, CP/CPPS is believed to be a group of diseases characterized by pelvic pain or discomfort, urinary abnormalities, and other symptoms, each with its unique etiology, clinical characteristics, and outcomes, likely resulting from the action of pathogens or (and) certain non-infectious factors. Traditionally, CP/CPPS was thought to be unrelated to bacterial infections. However, in recent years, with the development of microbiology and the advancement of high-throughput sequencing technology, an increasing number of studies have suggested that microorganisms in the reproductive system may play an important role in the pathogenesis of CP/CPPS. The unique characteristics of CP/CPPS, such as its refractory nature and tendency to recur, may be closely related to the microbiota and their biological functions in the reproductive system. The relationship between CP/CPPS and reproductive system microorganisms is one of the current hot topics in microbiology and urology, receiving considerable attention from scholars in recent years and making a series of new advances. Through this review, we will comprehensively explore the relationship between CP/CPPS and reproductive system microorganisms, and look forward to future research directions, aiming to provide new ideas and methods for clinical diagnosis and treatment, thereby improving the treatment outcomes and quality of life of CP/CPPS patients.